Wordwall-Assisted TGT Learning Models in The Solar System Materials: Its Impact on Improving Students' Concept Understanding - Astuti, Aldita Tasya; Zulirfan, Zulirfan; Ernidawati, Ernidawati (Journal of Natural Science and Integration, 2022)
The purpose of this study was to evaluate the impact of using the Teams Games Tournament (TGT) cooperative learning model on the conceptual understanding of seventh grade junior high school students. Experimental research with a quasi-experimental design "Nonequivalent control group design" and the research model "Posttest only control group design" is the methodology that will be used. The data collection tool was in the form of a test on the results of understanding the class VII concept of the Solar System material which consisted of 21 multiple choice questions. Descriptive analysis will be carried out with students' conceptual knowledge, and inferential analysis will be carried out with the normality test, homogeneity test, and hypothesis testing using SPSS version 22. After the analysis is carried out, it is known that the average understanding of the concept of the experimental group is 61.10 which is included in the high category, while the mean -the average control group's understanding of the concept of 53.33 is in the sufficient category. The difference in average understanding of concepts between the experimental group and the control group using the wordwall-assisted TGT cooperative learning model is statistically significant. Conclusion from the research: Compared to conventional learning, using the TGT cooperative learning methodology is effective in increasing students' conceptual understanding of the Solar System material.Keywords: Teams Games Tournament, Concept Understanding, Wordwall, Solar System